EVALUASI PROSES BELAJAR MENGAJAR PADA STMIK PROFESIONAL MAKASSAR - Rosnani (PROGRESS, 2016)
Tri Darma college covers, education, research and community service. The three components are interrelated with each other in supporting the success of teaching and learning in higher education. There are several factors to support teaching and learning activities, such as faculty-student ratio, frequency of attendance of lecturers in teaching and students in receiving lectures, as well as things that are non-technical.This research was conducted at the College of Informatics and Computer Management (STMIK) Profesional Makassar for year 2016 in Studies Program Information System, Information Management, Computer Engineering and Computerized Accounting Results showed overall good for the classroom theory and practical classes can be stated that the achievement of the highest number there on the course following the Computerized Accounting Information Management, Information Systems and lowest achievement is a program of study Computer Engineering. Their GPA for 7 semesters students from years 2012-2015 for Computerized Accounting Studies Program higher than that of the three other courses. Second-placed highest on the course for Information Management, Information System and the average low is IPS Computer Engineering study program.